Air-conditioning in residential buildings through absorption systems powered by solar collectors. (September 2017) - Tarsitano, Anna; Ciancio, Virgilio; Coppi, Massimo
Abstract: Over the past years, the scientific community has been exploring alternative solutions to the fossil fuels used for indoor air-conditioning. The solution here suggested is formed by absorption machines powered by solar panels used to air-condition small residential buildings. The study examined a small residential building and evaluated energy savings, reduction of CO2 and the return on investment compared to a traditional solution. The results obtained might be considered as valid since the heat used was provided by a free energy source with a low environmental impact, devoid of CO2 emissions.